Aureoboletus zunyiensis, a new species of Aureoboletus (Boletaceae, Basidiomycota) from Guizhou Province, China - Mo, Xing; Li, Ya-Dong; Chen, A-Min; Qi, Zhuo-Qiong; Li, Jing-Wei; Wen, Ting-Chi; Zhang, Wan-Ping; Xu, Xiu-Hong (Phytotaxa, 2026)
Aureoboletus zunyiensis from Guizhou Province, China, is described hereby on the basis of morphology and molecular analysis. It is characterized by a brownish-red pileal surface, yellowish context, ovoid to reniform spores, and cystidia are covered with a pale yellow refractive substance. Multigene analysis based on nrLSU, ITS, and TEF1-α supported that the new species belongs to Aureoboletus. Photographs, microstructure diagram, and a phylogenetic tree showing relationships to closely related taxa are provided.